Dynamic gut microbiome changes following regional intestinal lymphatic obstruction in primates. Issue 3 (September 2019) - Becker, F.; Gavins, F.N.E.; Fontenot, J.; Jordan, P.; Yun, J.Y.; Scott, R.; Polk, P.R.; Friday, R.E.; Boktor, M.; Musso, M.; Romero, E.; Boudreaux, S.; et al.
Abstract: The pathogenesis of inflammatory bowel disease (IBD) has been linked with lymphostasis, but whether and how lymphatic obstruction might disturb the intestinal microbiome in the setting of Crohn's Disease (CD) is currently unknown. We employed a new model of CD in African Green monkeys, termed 'ATLAS' (A frican green monkey t runcation of l ymphatics with obstruction a nd s clerosis), to evaluate how gut lymphatic obstruction alters the intestinal microbiome at 7, 21 and 61 days. Remarkable changes in several microbial sub- groupings within the gut microbiome were observed at 7 days post-ATLAS compared to controls including increased abundance of Prevotellaceae and Bacteroidetes-Prevotella-Porphyromonas (BPP), which may contribute to disease activity in this model of gut injury. To the best of our knowledge, these findings represent the first report linking lymphatic structural/gut functional changes with alterations in the gut microbiome as they may relate to the pathophysiology of CD.